1983
DOI: 10.1177/00220345830620011701
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure and Hardness of the Transparent of Human Carious Dentin

Abstract: The ultrastructure of the transparent layer of carious dentin was investigated in relation to hardness. This layer was the deeper part of the intermediately-softened inner carious dentin. Intratubular deposition of fine crystals was initially observed at the uppermost layer of normal dentin, increased in the subtransparent layer, and gradually shifted to deposition of rhomboid-shaped crystals in the transparent layer. Crystals were not seen in the tubules in the overlying discolored layer. Softening, due to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
130
1
21

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 8 publications
12
130
1
21
Order By: Relevance
“…The physical and chemical characteristics of caries-affected dentin are very different from those of normal dentin. Caries-affected dentin is softer than normal dentin because it is partially demineralized 11,[14][15][16] . Compared with normal dentin, crystals of intertubular caries-affected dentin are scattered and randomly distributed with larger apatite crystallites and wider inter-crystalline spaces 17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical and chemical characteristics of caries-affected dentin are very different from those of normal dentin. Caries-affected dentin is softer than normal dentin because it is partially demineralized 11,[14][15][16] . Compared with normal dentin, crystals of intertubular caries-affected dentin are scattered and randomly distributed with larger apatite crystallites and wider inter-crystalline spaces 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with normal dentin, crystals of intertubular caries-affected dentin are scattered and randomly distributed with larger apatite crystallites and wider inter-crystalline spaces 17) . Moreover, most tubules of caries-affected dentin are occluded with mineral deposits 15,16) . Electron probe microanalysis also showed that elemental contents are different between normal and caries-affected dentin surfaces 13) .…”
Section: Introductionmentioning
confidence: 99%
“…1 Caries-affected dentin contains intrinsic properties that are different from normal dentin, such as reduced permeability because of formation of whitlockites within the dentinal tubules and a partially demineralized intertubular dentin. [2][3] Ideally, in order to maximally preserve the tooth substrate, the clinical bonding substrate should be caries-affected dentin. However, during restorative preparations, it may be very difficult to avoid cutting into normal dentin due to the irregular shape of the caries lesion.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical guidelines for removal of this substrate are problematic and controversial. According to previous studies, the inner affected layer of carious dentin which is un-infected and remineralizable can be softer than normal dentin [1,2] or have similar properties to normal dentin. [3] These findings suggest that traditional tactile based characteristics of carious dentin often sacrifice more structure than necessary.…”
Section: Introductionmentioning
confidence: 95%
“…Carious dentin has a Knoop hardness that is less than that of normal dentin [1,15], indicating that it has a certain level of demineralization, even though the lumina of many of the dentin tubules are occluded with mineral crystals [18] to form the transparent layer. Dentin that is partially demineralized by caries may exhibit further mineral loss when it is treated with acidic bonding conditioners, resulting in a deeper penetration of adhesive resin and a thicker resin infiltrated layer formation during bonding.…”
Section: Introductionmentioning
confidence: 99%